An Open-Access Clicker Question Bank for Numerical Analysis. Issue 8 (14th September 2022) - Hossain, M. Alamgir; Menz, Petra M.; Stockie, John M.
ABSTRACT: We present a question bank consisting of over 250 multiple-choice and true–false questions covering a broad range of material typically taught in an introductory undergraduate course in numerical analysis or computational science. The questions are ideal for polling students during lectures by means of a student response system that uses clicker remotes or smartphones running a suitable app. We describe our experiences implementing these clicker questions in a recent class and provide evidence of their effectiveness in terms of testing students' prior knowledge, gauging understanding of new material, increasing participation, and especially improving student satisfaction. Our conclusions are supported by a mid-semester student survey as well as anecdotal observations. The question bank has been released as an open-access educational resource under a Creative Commons license (CC BY-NC-SA) for free use by the mathematics community.